The oxidative and biological destruction of composite materials based on low-density polyethylene and lignocellulosic fillers - Pantyukhov, Piotr; Monakhova, Tatyana; Kolesnikova, Nataliya; Popov, Anatoly; Nikolaeva, Svetlana (Publishing House of Lviv Polytechnic National Universito, 2012)
In this work 20 new biogegradable materials from polyethylene and lignocellulosic fillers were examined. The samples with and without compatibilizer were compared. This work contains four different methods of investigation: TGA, microscopy, thermal oxidation, biodegradation in soil. Досліджено 20 нових біодеградабельних матеріалів на основі поліетилену та лігноцелюлозних наповнювачів. Проведено порівняння зразків з компатабілізаторами та без них використовуючи різні методи досліджень: ТГА, мікроскопічні дослідження, термічне окиснення, біодеградацію в грунті.
Оксидаційна та біологічна деструкція композитних матеріалів на основі поліетилену низької густини та лігноцелюлозних наповнювачів
Keywords: banana skin; biodegradable polymer; lignocellulosic filler; polyethylene; sodium lignosulfonate; sunflower husk; бананова шкіра; біодеградабельний полімер; лігноцелюлозний наповнювач; поліетилен; лігносульфат натрію; насіння соняшника